Extraction of an active enzyme by self-buffering ionic liquids: a green medium for enzymatic research. Issue 22 (15th February 2016) - Gupta, Bhupender S.; Taha, Mohamed; Lee, Ming-Jer
Abstract : The extraction of a model enzyme α-chymotrypsin in its active conformation from an aqueous solution by using new biocompatible and self-buffering Good's buffer ionic liquids-based aqueous biphasic systemsis demonstrated. Abstract : In this work, the extraction of a model enzyme α-chymotrypsin in its active conformation from an aqueous solution by using new biocompatible and self-buffering Good's buffer ionic liquids (GBILs)-based aqueous biphasic systems (ABSs) is demonstrated. The experimental liquid–liquid phase boundary data for these new GBIL-based ABSs were measured at 298.2 K. These new ionic liquids are derived from biological Good's buffers as anions and tetra-alkylammonium as cations. The buffering potential of these GBILs was confirmed by measuring their pH profiles and protonation constants (p K a ) in aqueous solution by a potentiometric method at various temperatures. Moreover, these GBILs provide a greater stabilizing effect on the activity of α-chymotrypsin, as compared with the corresponding Good's buffers. Therefore, the new self-buffering GBILs may not only serve as a biocompatible medium for enzymatic research, but also avoid the use of an external buffering agent, which is often needed for pH control in the case of using a conventional ILs-based medium. Therefore, these new biocompatible GBILs are more advantageous over the conventional ILs-based media for enzymatic research.